A Cross-Cultural Analysis of Personality Structure Through the Lens of the HEXACO Model. Issue 1 (2nd January 2017) - Ion, Andrei; Iliescu, Dragos; Aldhafri, Said; Rana, Neeti; Ratanadilok, Kattiya; Widyanti, Ari; Nedelcea, Cătălin
ABSTRACT: Across 5 different samples, totaling more than 1, 600 participants from India, Indonesia, Oman, Romania, and Thailand, the authors address the question of cross-cultural replicability of a personality structure, while exploring the utility of exploratory structural equation modeling (ESEM) as a data analysis technique in cross-cultural personality research. Personality was measured with an alternative, non–Five-Factor Model (FFM) personality framework, provided by the HEXACO–PI (Lee & Ashton, 2004 ). The results show that the HEXACO framework was replicated in some of the investigated cultures. The ESEM data analysis technique proved to be especially useful in investigating the between-group measurement equivalence of broad personality measures across different cultures.